Isolasi dan identifikasi bakteri dari produk fermentasi telur ikan tambakan (Helostoma temminckii C.V): Isolation and identification of bacteria from fermented kissing gourami fish roes (Helostoma temminckii C.V) - Rafitah Hasanah (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2022)
Kissing gourami fish roes is a traditional salt fermented fish product widely consumed in east Kalimantan. This product is still made traditionally by applying spontaneous fermentation with added salt. This research aimed to isolate and identify bacteria found in fermented kissing gourami fish roes. The research consists of three steps: producing, isolating and bacteria-identifying. In this research kissing gourami fish roes has been fermented for one year so that fish roes fermented can be obtained. Those colonies were isolated and preserved using tryptic soy agar (TSA) media and determined using BBL Crystal method. The results described 5 (five) different colony of bacteria grew dominantly. The bacteria were identified as Bacillus megaterium, Leifsonia aquatica, Corynebacterium propinquum and Lysinibacillus sphaericus.